Regulations concerning the curriculum in the gymnasium (Statens Trykningskontor, 1965)
Comprehensive statements of regulations concerning courses of study in both lines of the gymnasium - the Linguistic and the Mathematical. Under each subject, the statement of course objectives, instructural methods, and examination requirements are given.